Evaluation of irreversibility in an ammonia-water absorption refrigeration system using three different mathematical models to calculate the thermodynamic properties - Vera-Romero, Iván; Heard-Wade, Christopher Lionel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Second Law or Exergy Analyses of Absorption Refrigeration Systems (ARS) are very important for optimisations based on available work; these analyses are derived from the operating conditions and property calculations. There are several methods available for calculating the thermodynamic properties used in modelling these systems. A thermodynamic study on an ARS with the ammonia-water mixture (base case) was carried out with the objective of analysing the sensitivity of the overall and individual component irreversibility to the thermodynamic property. To this end, three existing methods were used: (M1), a model proposed by Ibrahim and Klein (1993) and used in the Engineering Equation Solver (EES) commercial software; (M2), a model proposed by Tillner-Roth and Friend (1998) and embodied in REFPROP v.8.0 developed by the National Institute of Standards and Technology (NIST); and (M3), a method proposed by Xu and Goswami (1999) that was programmed for this analysis. The obtained differences in the properties and the first law performance of the ARS are insignificant in the determination of the coefficient of performance (COP) (base case: 0.595, M1: 0.596, M2: 0.594, M3: 0.599). For the second law analysis, the overall irreversibility was the same (123.339kW) despite the irreversibilities per component had important differences: the solution heat exchanger (M1: 5.783kW, M2: 6.122kW, M3: 8.701kW), the desorber (generator) (M1: 51.302kW, M2: 45.713kW, M3: 49.098kW) and the rectifier (M1: 0.766kW, M2: 3.565kW, M3: 0.427kW). The components that destroy exergy the most are the desorber, the absorber and the condenser.